2016
DOI: 10.2220/biomedres.37.77
|View full text |Cite
|
Sign up to set email alerts
|

<b>Clinicopathological significance of gastric poorly differentiated medullary car</b><b>cinoma </b>

Abstract: Poorly differentiated gastric adenocarcinoma of solid type is known to show a clinicopathological diversity, but its morphological characteristics have rarely been investigated. In this study, we defined poorly differentiated medullary carcinoma indicating the following three characteristics: (i) more than 90% of the entire tumor were composed of poorly differentiated adenocarcinoma in a medullary growth, (ii) the tumor exhibited an expansive growth at the tumor margin, and (iii) special types such as an α-fet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
(17 reference statements)
1
7
1
Order By: Relevance
“…Thus, morphology, MSI, and biological behavior in solid-type PDA are different from those in non-solid-type PDAs. There have only been a few pathological reports until now, and the details regarding solid-type PDA of the stomach remain obscure [4,[10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, morphology, MSI, and biological behavior in solid-type PDA are different from those in non-solid-type PDAs. There have only been a few pathological reports until now, and the details regarding solid-type PDA of the stomach remain obscure [4,[10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Gastric medullary carcinoma, a new WHO diagnostic entity, is a very rare subtype of gastric cancer that is histologically characterized by a sharply demarcated, poorly differentiated carcinoma with organoid/syncytial growth pattern with pushing borders and an associated lymphocytic inflammatory response [ 1 , 7 ]. It is typically seen in elderly men, associated with MSI-H, presents at an early clinical and pathologic stage, and has an improved prognosis compared to gastric cancers of other special types [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the synonymous determination by the WHO, gastric medullary carcinoma is frequently associated with microsatellite instability-high (MSI-H), while lymphoepithelioma-like carcinoma is associated with Epstein Barr Virus (EBV) infection [ 4 6 ]. Gastric medullary carcinoma has been defined histologically as comprising more than 90% of poorly differentiated solid type adenocarcinoma with associated lymphocytic infiltrate, demonstrating pushing growth pattern at the tumor edge, and excluding other special types of gastric carcinoma [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gastric cancer remains the third leading cause of cancer death worldwide. Although it is commonly supposed that PDA has a worse prognosis than other histological types, several studies showed that PDA with solid morphology is associated with a favorable prognosis despite its poorly differentiated histology . According to the Japanese classification, PDAs are divided into the solid‐type and nonsolid‐type…”
Section: Introductionmentioning
confidence: 99%
“…Although it is commonly supposed that PDA has a worse prognosis than other histological types, several studies showed that PDA with solid morphology is associated with a favorable prognosis despite its poorly differentiated histology. [1][2][3][4] According to the Japanese classification, PDAs are divided into the solid-type and nonsolid-type. 5 Solid-type PDAs often contain a glandular component that tends to be detected superficially in the tumor, suggesting that solid-type PDAs develop from a tubular or papillary adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%